RARE CALCIFYING EPITHELIAL ODONTOGENIC TUMOR IN A HIV POSITIVE INDIVIDUAL - Sundaragiri, Krishna Sireesha; Mittal, Sankalp; Sankhla, Bharat; Saxena, Shikha; Shekhawat, Chandni; Bhargava, Akshay (Journal of Ayub Medical College Abbottabad, 2021)
The calcifying epithelial odontogenic tumour (CEOT) is a rare but well recognized benign odontogenic tumour for any Pathologist. Histologically, it shows sheets of polyhedral epithelial cells with prominent intercellular bridges, hyperchromatic nuclei and globules of amyloid-like material among tumour cells which undergoes calcification. We present a case of CEOT with classical histopathological picture in a 37-year-old HIV positive patient with long evolution history. Its association with HIV positivity, long clinical history and delay in surgical treatment make it a challenging case to report. Keywords: Calcifying Epithelial Odontogenic Tumour, HIV